Use of set retarders in concrete with aggregates from the city of Teófilo Otoni (Research, Society and Development, 2022)
This work sought to analyze the variation of strength and workability of concrete mixes with the presence of a chemical additive that retards setting, in its minimum and maximum dosage with Teófilo Otoni aggregates. Eighty-one concrete specimens were made, which were later subjected to the consistency test, incorporated air content and axial compressive strength with rupture ages of 7, 14 and 28 days. Set-modifying additives are intended to provide better workability and handling to concrete, such as the set-retarding additive that inhibits cement hydration in order to delay the initial setting of the concrete. Three traits were defined T1 (w/c 0.90 low in cement), T2 (w/c 0.70 intermediate in cement) and T3 (w/c rich in cement), with expected theoretical values ​​of 18 MPa, 25 MPa and 40 MPa, respectively. The best result was obtained with the T3AR7 mix, which at 28 days reached 51.27 MPa of strength. Significant gains in strength of concrete with setting retarding additive were observed, reaching 37.09% higher strength compared to T1SA, 17.96% compared to T2SA and 11.86% to T3SA, in its minimum dosage. At maximum dosage, it achieved superior performance of 44.79% with T1AR7, 34.65% with T2AR7 and 15.60% with T3AR7, which obtained resistances of 32.71 MPa, 44.22 MPa and 51.27 MPa, respectively. In general, the retarding additive in its minimum dosage obtained a better performance in relation to strength and cost-effectiveness in concrete.